Commitment organizational in the management administrative of the National University Hermilio Valdizan, Huanuco, Peru - Pillco Primo, Susan Carol (2023)
Objective. The study sought the influence to evaluate of the commitment organizational on the management of the staff administrative at the National University Hermilio Valdizan, Huanuco, 2022. Methods. The type of study was applied, explanatory level and design non-experimental - cross-sectional. The sample remained constituted by 30 workers administrative and was obtained by sampling non-probabilistic of type intentional, taking into account the selection criteria. Were used two instruments for the collection of data; the first was the organizational commitment inventory, with 21 questions, and the second was the administrative management questionnaire, with 40 questions. Were used two instruments for the collection of data; the first was the organizational commitment inventory, with 21 questions, and the second was the questionnaire for the management administrative, with 40 questions. Both were validated by the judgment of experts to determine their validity of content and was applied the coefficient alpha of Cronbach's to determine reliability, obtaining an index of 0.985 for the instrument of commitment organizational and of 0.988 for the instrument of management administrative. Results. The results show a commitment organizational healthy in a 90 %, an excellent administrative management in a 49 % and a relationship between the variables of a level high with 97.2 %. Because to that p = 0.000 < 0.05 and r = 0.972, was accepted the hypothesis study. Conclusion. In relation to the general objective it was determined that the commitment organizational influences on the management administrative of the staff administrative of the National University Hermilio Valdizan, Huanuco, 2022, since it exists between the variables an relationship in a level high with 97.2 %.